A Comprehensive Gene Expression Profile of Pectin Degradation Enzymes Reveals the Molecular Events during Cell Wall Degradation and Pathogenesis of Rice Sheath Blight Pathogen Rhizoctonia solani AG1-IA - Talluri Bhaskar Rao (Journal of Fungi, 2020)
Sheath blight disease of rice caused by Rhizoctonia solani Kühn (teleomorph: Thanatephorus cucumeris) remains a global challenge due to the absence of reliable resistance genes and poor understanding of pathogen biology. Pectin, one of the most vital constituents of the plant cell wall, is targeted by pectin methylesterases, polygalacturonases, and few other enzymes of fungal pathogens. In this study, we catalogued the expressed genes of the fungal genome from RNAseq of R. solani infected four rice genotypes. Analysis of RNAseq revealed 3325 pathogen genes commonly expressed in all rice genotypes, in which 49, 490, and 83 genes were specific to BPT5204, Tetep, and Pankaj genotypes, respectively. To identify the early and late responding genes of R. solani during plant cell wall degradation, a real-time PCR analysis of 30 pectinolytic enzymes was done at six different time points after inoculation. The majority of these genes showed maximum induction at the 72 h time point, suggesting that it is the most crucial stage of infection. Pankaj showed lesser induction of these genes as compared to other genotypes. Leaf-blade tissue and 45 days old-growth stage are more favorable for the expression of pectin degradation genes of R. solani. Additionally, the expression analysis of these genes from four different strains of R. solani suggested differential regulation of genes but no distinct expression pattern between highly virulent and mild strains. The implications of the differential regulation of these genes in disease development have been discussed. This study provides the first such comprehensive analysis of R. solani genes encoding pectin degrading enzymes, which would help to decipher the pathogen biology and sheath blight disease development.